2020
DOI: 10.15253/2175-6783.20202144194
|View full text |Cite
|
Sign up to set email alerts
|

Maternal difficulties in home care for newborns

Abstract: Objective: to analyze the association between maternal difficulties in home care for newborns and parity. Methods: cross-sectional study, carried out in Primary Health Care in a Brazilian municipality. The sample consisted of 247 puerperal women, whose data collection took place by using two questionnaires, applied in home visits. The data were analyzed using Pearson’s chi-square test. Results: it was observed that both primiparous and multiparous women had a very high percentage of difficulties related to car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
3
0
7
Order By: Relevance
“…A study conducted in Brazil, published in 2020 with the participation of 247 postpartum women aged between 20 and 34, revealed that 57.6% felt insecure about holding the baby due to its size. Additionally, 35.9% reported difficulties in holding the baby in the bathtub, 30.4% expressed fear of washing the baby’s back and genitals, 21.7% had questions about cleaning the baby’s head and face, and 12% had concerns about drying the neonate ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Brazil, published in 2020 with the participation of 247 postpartum women aged between 20 and 34, revealed that 57.6% felt insecure about holding the baby due to its size. Additionally, 35.9% reported difficulties in holding the baby in the bathtub, 30.4% expressed fear of washing the baby’s back and genitals, 21.7% had questions about cleaning the baby’s head and face, and 12% had concerns about drying the neonate ( 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a study conducted in Paraná, Brazil, underscored the necessity to understand maternal emotions during the hospitalization of the premature newborn and after discharge. This focus is crucial as emotions such as fear, insecurity, and concern can influence home care ( 9 ) . Concurrently, a study in China stressed the value of healthcare professionals offering care and guidance to families of premature infants, drawing insights from listening to parents’ experiences and concerns ( 11 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo realizado com 54 puérperas em 20 Estratégias de saúde da família no sudoeste do Paraná, cujo propósito foi analisar a associação entre dificuldades maternas no cuidado domiciliar a recém-nascidos e paridade. Teve como resultado da comparação entre as dificuldades vivenciadas por puérperas primigestas e multigestas que ambas possuíam dúvidas semelhantes no cuidado domiciliar a recém-nascidos, estando principalmente associadas à insegurança, à preocupação e ao desamparo (Costa, 2020).…”
Section: Subcategoria Iii-inexperiência Maternaunclassified
“…Algumas questões adicionais com o banho também devem ser levadas em conta, como os produtos que devem ser usados, a temperatura ideal da água do banho, a maneira para lavar a cabeça, o rosto, as costas e os genitais, além da melhor técnica para segurar e secar o bebê, o que geralmente está envolto de muita insegurança por parte dos familiares cuidadores por ser um ser tão pequenino e frágil. Com isso, o banho de um recém-nascido é um procedimento complexo, que gera dúvidas e incertezas para sua realização, especialmente pelo receio do bebê deslizar e cair na banheira 4 .…”
Section: /13 Introduçãounclassified